Recreational and environmental markets for forest enterprises: a new approach towards marketability of public goods - Mantau, U.; Mantau, U.; Merlo, M.; Merlo, M.; Sekot, W.; Sekot, W.; Welcker, B.; Welcker, B. (Wallingford :CABI Publishing, 2001)
This book is the published outcome of the RES project (Niche markets for recreational and environmental services from multiple forest production systems) funded by the European Commission. The book discusses the project's leading ideas, basic assumptions, summary and recommendations; an analysis of case studies in Germany, Italy, Austria and The Netherlands; economic strategies for transformation and product development; marketing tools for the development of RES products; contracts and organizations as a basis of market development; multifunctional forest management; delimitation of property rights; and an analysis of forest policy including evaluation studies of public acceptance.
Keywords: EE112 - Forestry Economics, (New March 2000); EE119 - Leisure, Recreation and Tourism Economics, (New March 2000); EE700 - Marketing and Distribution; KK100 - Forests and Forest Trees (Biology and Ecology); KK110 - Silviculture and Forest Management; KK500 - Forest Products and Industries (General); UU610 - Recreational Facilities and Management, (New March 2000); UU700 - Tourism and Travel; Austria; Europe; Germany; Italy; Netherlands